Impact of anti-PEG antibodies induced by SARS-CoV-2 mRNA vaccines - Ju, Yi; Carreño, Juan Manuel; Simon, Viviana; Dawson, Kenneth; Krammer, Florian; Kent, Stephen J. (Nature reviews. Immunology, 2023)
The successful mRNA vaccines against COVID-19 contain polyethylene glycol (PEG) to stabilize the lipid nanoparticles. Recent data show that PEG-specific antibodies can be induced or boosted by mRNA vaccination. Further research is needed to study the potential links between PEG-specific antibodies, vaccine reactogenicity and enhanced clearance of other PEG-containing medicines.